Chronic and Recurrent Pain - Carl L. von Baeyer (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
For many years people assumed that children did not experience chronic pain. However, recent epidemiological studies show that chronic pain, defined as constant or recurrent pain lasting three months or longer, is common in childhood. Empirical studies have characterized chronic pain conditions including headaches, abdominal pain, chest pain, and musculoskeletal pains including fibromyalgia. These pain conditions are associated with school absence, emotional distress, disruption in family activities, and significantly reduced quality of life in both the affected child and their families. For some of these children, chronic pain persists from childhood into adulthood, causing substantial long-term personal and financial costs to the individual, society, and our health care systems. Despite the prevalence and serious consequences of pediatric chronic pain, it is still under-recognized and under-treated. Too often, chronic pain is treated as a symptom of something else, rather than as a separate condition requiring its own treatment. The goal of this Special Issue was to discuss recent advances in the understanding and treatment of pediatric chronic pain. The Special Issue Book contains 22 notable articles including original research, reviews, and commentaries. Together they provide an excellent overview of the field of chronic and recurrent pediatric pain as it stands in 2016-2017.